Do adverse childhood experiences increase the risk of postdeployment posttraumatic stress disorder in US Marines? - Ryan Margaret AK; Smith Besa; LeardMann Cynthia A (BMC, 2010)
Abstract Background Posttraumatic stress disorder (PTSD) has been associated with combat intensity, lack of social support, and adverse childhood factors among military personnel in previous studies. It has not been well established if adverse childhood experiences reported predeployment are independently associated with postdeployment PTSD. Methods Data were evaluated from 8,391 male responders of the Recruit Assessment Program survey at Marine Corps Recruit Depot in San Diego who were deployed in support of military conflicts between September 2001 and June 2004. Using patient medical records to determine PTSD diagnoses, Cox proportional hazard modeling was performed to examine if adverse childhood experiences were independently associated with postdeployment PTSD. Results After adjustment, those who reported adverse childhood experiences in more than one category were significantly more likely to be diagnosed with postdeployment PTSD. Specifically, childhood physical neglect was mostly strongly associated with postdeployment PTSD. Conclusions Findings suggest that Marines who experience multiple types of adverse childhood experiences may be at increased risk for postdeployment PTSD. It is possible, however, that these results indicate that men willing to report childhood adverse experiences are also more willing to seek care for PTSD.